Module-assembly of injectable cellular DNA hydrogel via clickable cells and DNA scaffolds - Nam, Hyangsu; Jeon, Hyunsu; Kim, Hyejin; Yoon, Hong Yeol; Kim, Sun Hwa; Lee, Jong Bum (Elsevier BV, 2023)
In regenerative therapy, artificial extracellular matrix (ECM)-embedded cells are implanted to exert therapeutic effects in vivo. Often, artificial ECM fails to achieve the required tissue compatibility to promote cell-to-cell communication and retention of cells at the target site. To address this challenge, we introduced a unique breathing therapeutic matrix fabricated by the covalent unit assembly of a DNA microscaffold (DNA microscaf) with therapeutic mammalian cells. In our system, metabolically engineered cells serve as active building units for the final construct as well as therapeutic agents. In contrast, a DNA microscaffold with a pre-assigned clickable moiety serves as a depot for cells to maintain biological functions for subsequent in vivo localization. Notably, the final construct has ultra-soft mechanical properties, enabling the injection of an intact therapeutic matrix without surgery. The active linkages between the cells and scaffolds are gradually diluted as the cells proliferate, allowing the dislodging of cells. The subsequent slow disintegration of the cellular DNA hydrogel also allows for the successful replacement of the damaged tissue.